2020
DOI: 10.3389/fspor.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Wide Skis As a Potential Knee Injury Risk Factor in Alpine Skiing

Abstract: Alpine skis with wider waist widths have recently become more popular. With such skis, the contact point of the ground reaction force during ski turns is displaced more medially from beneath the sole of the outer ski, which may present an increased risk of injury. The aim of this study was to investigate knee joint kinetics, kinematics, and lower limb muscle activation as a function of changes of the ski waist width in a laboratory setting. A custom skiing simulator was constructed to enable simulation of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…Notably, tail width failed to reach statistical significance with p=0.082. These results do not confirm other work suggesting that skis with larger waist widths are associated with an elevated risk for injury on hard snow 29 32. In competitive skiing, the International Ski Federation (FIS) regulated in most disciplines the maximal waist width to be typically ≤65 mm 32.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Notably, tail width failed to reach statistical significance with p=0.082. These results do not confirm other work suggesting that skis with larger waist widths are associated with an elevated risk for injury on hard snow 29 32. In competitive skiing, the International Ski Federation (FIS) regulated in most disciplines the maximal waist width to be typically ≤65 mm 32.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous work has started to examine the relationship between ski width and knee injury. For wider skis, the contact point of the ground reaction force during ski turns is displaced more medially beneath the sole of the outer ski 29. In a study with expert skiers conducted on hard and frozen snow conditions on a ski slope, Zorko et al 10 found that an increased ski width at the waist reduced the mean abduction (knee valgus) and increased external rotation of the lower leg of the outer ski.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To a certain extent, this latter problem can be attenuated by smoothing/maintaining the track between runs. In addition, accurate geodetic GNSS systems can help ensure that the course gates are placed in exactly the same locations on several days in a row [73]. In any case, snow conditions, which can significantly affect the level of friction between the skis and ground [4], length of the course, shape of the turns, speeds, etc., must be carefully monitored, especially when investigating performance [22,58].…”
Section: Sample Sizementioning
confidence: 99%